All-Cause Mortality Risk Associated With Solid Fuel Use Among Chinese Elderly People: A National Retrospective Longitudinal Study - Shen, Shisi; Luo, Min; Meng, Xuchen; Deng, Ying; Cheng, Shuwen (Frontiers in Public Health, 2021)
Background The adverse health effects of air pollutants are widely reported, and the elderly are susceptible to toxic environments. This study aimed to identify the all-cause mortality associated with cooking fuel use among the elderly. Methods A total of 5732 and 3869 participants from the Chinese Longitudinal Healthy Longevity Survey were enrolled in two (2014–2018) and three waves (2011–2018) of survey. Cooking fuel was divided into clean and solid fuel. Cox proportional hazards models were used to estimate the mortality hazard ratio (HR). Subgroup analyses were performed to assess the potential interaction effect. Results The 5732 participants who reported using solid fuel (53.47%) were associated with higher HR (9.47 per 100 person-years, n=1743) (HR=1.09, 95% CI=1.01–1.18) in 2011–2018. The 3869 participants who reported change of using cooking fuel in 2011–2014, stable solid fuel use was were associated with higher HR (5.07 per 100 person-years, n=509) compared with those using clean fuel, and the participants who changed cooking fuel had a marginally significant relationship with increased mortality risk (5.42 per 100 person-years, HR=1.14, 95% CI=0.99–1.31). Interaction and stratified analyses showed that solid fuel use had a remarkable effect on mortality in participants who were non-current smokers, had low dietary diversity scores, and were living in areas with high PM2.5 concentrations (>50 μg/m3) and city population below 8 million (P for interaction < 0.05). The association was robust in the three sensitivity analyses. Conclusion The findings show the steady association between solid fuel use and mortality among the Chinese elderly, and smoking status and PM2.5 concentration synergistically enhance this association.